SULT1A1 genetic polymorphisms and the association between smoking and oral cancer in a case-control study in Brazil - Koifman, Sergio (Frontiers in Oncology, 2012)
Introduction: Oral cancer is a public health problem worldwide, being tobacco and alcohol consumption their main risk factors. Sulfotransferase 1A1 (encoded by SULT1A1) is involved in procarcinogens metabolism, such as polycyclic aromatic hydrocarbons present in tobacco smoke. Objective: The aim of this study was to explore the magnitude of association between SULT1A1 gene Arg213His polymorphism and oral cancer, and to explore the interaction between such polymorphism and smoking. Methods: A hospital-based case-control study was carried out in Rio de Janeiro, Brazil, during 1998-2002. Epidemiological data and biological samples were obtained from 202 oral cancer patients and 196 sex and age-frequency matched controls without cancer antecedents. Results: No association was observed between Arg213His SULT1A1 polymorphism and oral cancer risk in overall analysis (OR=1.06, 95% CI 0.71-1.57). Among smokers, however, the presence of at least one polymorphic allele (genotypes Arg/His and His/His versus Arg/Arg) was associated with oral cancer risk (OR = 2.72, 95% C.I.1.15-6.43). Conclusion: Our results suggest that Arg213His SULT1A1 polymorphism may modulate the association between smoking and oral cancer. However, this association needs to be replicated in other studies: due to modest number of cases and controls, the role of chance in the observed association cannot be ruled out.